1985
DOI: 10.1177/002246698501900412
|View full text |Cite
|
Sign up to set email alerts
|

Mainstreaming Programs: Design Features and Effects

Abstract: The twofold goal of this study was to review and analyze the design features and efficacy of mainstreaming as an educational approach to serving disabled students. Based on a predetermined set of criteria, 11 empirical studies of the effects of mainstreaming published from 1975 through spring, 1984 were selected for analysis from a total pool of 264 studies. Meta-analysis was the technique used to perform a quantitative synthesis of findings from the studies.Among the notable findings was that mainstreamed dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
30
0
3

Year Published

1988
1988
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 94 publications
(36 citation statements)
references
References 18 publications
1
30
0
3
Order By: Relevance
“…In the field of education, meta-analysis has been used to assess the relation between classroom size and achievement (e.g., McGiverin, Gilman, & Tillitski, 1989) and to examine the efficacy of mainstreaming programs for special education students (e.g., Wang & Baker, 1985). In the medical sciences, meta-analysis has been used in multiple areas including, for example, an examination of the relationship between breast cancer risk and mammography screening (McCaul, Branstetter, Schroeder, Glasgow, 1996).…”
Section: Popularity and Increased Usage Of Meta-analysismentioning
confidence: 99%
“…In the field of education, meta-analysis has been used to assess the relation between classroom size and achievement (e.g., McGiverin, Gilman, & Tillitski, 1989) and to examine the efficacy of mainstreaming programs for special education students (e.g., Wang & Baker, 1985). In the medical sciences, meta-analysis has been used in multiple areas including, for example, an examination of the relationship between breast cancer risk and mammography screening (McCaul, Branstetter, Schroeder, Glasgow, 1996).…”
Section: Popularity and Increased Usage Of Meta-analysismentioning
confidence: 99%
“…However, after reviewing a larger number of studies which involved children with behavioral disorders, mental retardation, and learn ing disability, these authors concluded that "little evidence exists supporting the efficacy of special education or the development of differential programs as a result of the assessment-placement process" (p. 243). Wang and Baker (1986) conducted a meta-analysis of 11 studies which set out to examine the efficacy of mainstreaming versus special classes. Of a total of 541 students of preschool, elementary school, and middle school ages, 3% were learning disabled.…”
Section: Poor Readers With Ld In Special Ld Remedial Programsmentioning
confidence: 99%
“…Studies into the effects of special versus regular placement for children with disabilities date back into the 1930s (Carlberg & Kavale 1980). Three meta‐analyses (Carlberg & Kavale 1980; Wang & Baker 1985/86; Baker et al . 1994/95) conclude that placement in a regular class leads to small to moderate positive effects on cognitive and social development of students with intellectual disabilities (ID).…”
Section: Introductionmentioning
confidence: 99%